L1 as a Semiotic Tool: Deconstructing Grammatical Scaffolding in a Low-Exposure EFL Context in Indonesia - Feisal Aziez; Novan Andrianto; Arifin Muslim; Aleeyah Masae; John Louie Domingo Galang (WISE Pendidikan Indonesia, 2026)
The instruction of abstract grammatical concepts, such as the Present Continuous Tense, presents significant cognitive challenges for Young Learners in English as a Foreign Language (EFL) context, particularly where exposure to the target language is limited. While traditional